Digital Entrepreneurship Transformation Through Utilization Of NFT, AI, and Blockchain in Innovation Models, Regulations, ans Their Impacts to Economy Creative - Teuku Isnaini; Zikrul Khalid; Boihaki Boihaki; Maisarah Maisarah (Jurnal Pendidikan, Sains Sosial, dan Agama, 2025)
Urgency of research This urge done Because digital transformation has become driver main change in economy creative, especially through utilization Non-Fungible Token (NFT) technology, Artificial Intelligence (AI), and Blockchain. technology This present opportunity new in monetization digital works, creative process automation, and security transaction Web3 based. However, adoption technology this is still in Indonesia face various challenges, including limitations regulation, low digital literacy, and barriers infrastructure. Research This aim For analyze the influence of NFT, AI, and Blockchain on growth digital entrepreneur income, assess relatedness between regulations and levels adoption Web3 technologies, as well as formulate innovative strategies and policies adaptive support ecosystem economy creative. Research Methods use Mixed Method approach, with survey to perpetrator industry creative and interview deep as well as studies case For understand dynamics adoption Web3 technology. Research Results show that The application of NFT, AI, and blockchain is not not only relevant, but also strategic For encourage digital entrepreneurship transformation, with the note need the existence of an inclusive Web3 business model as well as policy adaptive based evidence technology This can contribute sustainably to strengthening ecosystem economy creative in Indonesia